Pembinaan yang Dilakukan Kepala Sekolah dan Etos Kerja Guru-guru Sekolah Dasar - Zahera Sy (Universitas Negeri Malang, 2016)
This research was aimed at exploring teachers' opinion on supervision implemented by school principals and their work ethos. A proportional random sampling was applied to select 102 teachers from 47 elementary schools in Musi Banyuasin, South Sumatra. Data were collected by questionnaire and analysed using persentage and product moment correlation. The result revealed that supervision implemented by school principals was good enough, that teachers' work ethos could be categorized as high, and that there was a positive correlation between guidance given by school principals give more guidance to their teachers, especially in making instructional design and providing teaching-learning facilities